(untitled) (IUBAT Review, 2024)
This paper presents a dumbbell-shaped patch antenna designed for biomedical applications. The antenna is powered through an insect-fed transmission line, and its resonance frequency is found within the Industrial, Scientific, and Medical (ISM) band, ranging from 2.3408 to 2.5546 GHz. The substrate of the antenna is chosen as FR-4 (with a relative permittivity of 4.3 and a loss tangent of 0.0004), while the superstrate, which isolates the radiating patch and ground, is made of Al₂O₃ (with a relative permittivity of 9.4 and a loss tangent of 0.004). The antenna design is simple, utilizing only a shorting pin to achieve the desired operating frequency of 2.444 GHz. To evaluate its performance as a transmitter antenna and its link budget with an external receiver antenna, the antenna is numerically constructed within a three-layer human tissue phantom consisting of skin, fat, and muscle layers. The proposed antenna, with compact dimensions of 8 × 5.5 mm², can communicate with the receiver antenna at a distance of approximately 9 m with 1 Mbps data speed. The antenna exhibits an impedance of 49.89–j0.16Ω, which is close to the desired source impedance of 50Ω. Furthermore, it demonstrates improved bandwidth, gain, and specific absorption rate (SAR) compared to some recent well-known papers. IUBAT Review—A Multidisciplinary Academic Journal, 7(2): 64-84